(untitled) - Deddy Kurniawan Halim; Syamsul Alam Paturusi; Wayan Suardana; Sulistyawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This is a preliminary study to develop an instrument of n-GreenV that measures the need for Green Village to find out the feasibility of tourism village in response to the trend of tourist growth in Bali that has been moving from mass tourism in urban area the ecotourism in rural area. The measurement used two exogen variables: Perception on Sustainable Tourism and Perception on Green Tourist. One moderating variable named Community P: Perception participation in determining the need of Green Village and the type of Green Village. The study employed 30 villagers of Bongan Village. It used the PLS (Partial Least Square) method to get a Structural Equation Model for the instrument’s construct where items with p ? 0,10 will be terminated and excluded from the instrument. Results shows that 3 indicators of dimension Environment (p=0,137; p= 0,126; p=0,363), 1 indicator of dimension Social (p=0,126) both of the variable Perception on Sustainability, and 3 indicators of dimension Environment Load (p=0,410; p=0,364; p=0,639), 3 indicators of dimension Conservation Effort (p=0,211; p=0,539 ;p=0,158) both of the variable Perception on Green Tourist, and 2 types of attraction of the variable Green Village are not valid, which are Cultural Tourism (p=0,246) and Adventure Tourism (p=0,534). The villagers preferred the remaining types: Nature Tourism (p=0,00) and Agritourism (p=0,029).